1995
DOI: 10.2165/00002018-199513030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Antagonists

Abstract: The interaction of calcium antagonists, including the dihydropyridine calcium antagonists (e.g. nifedipine), verapamil and diltiazem, with drugs from other classes has major clinical ramifications as the use of drug combinations increases in frequency. Combinations are used in the treatment of disorders ranging from hypertension to cardiac rhythm disturbances, angina pectoris and peripheral vasospastic disease. In this era of organ transplantation, drugs like cyclosporin are coming into potential conflict with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 184 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…However, it is known that calcium channel antagonists sometimes give rise to clinical drugdrug interactions. [1][2][3][4] As one possible explanation for such drug-drug interactions, the inhibition of cytochrome P450 (P450) enzymes, especially CYP3A subfamily enzymes, by calcium channel antagonists has been proposed. 5,6) On the other hand, several calcium channel antagonists have also been reported to induce CYP2B and CYP3A subfamily enzymes in the rat liver [7][8][9] and human primary cultured hepatocytes.…”
mentioning
confidence: 99%
“…However, it is known that calcium channel antagonists sometimes give rise to clinical drugdrug interactions. [1][2][3][4] As one possible explanation for such drug-drug interactions, the inhibition of cytochrome P450 (P450) enzymes, especially CYP3A subfamily enzymes, by calcium channel antagonists has been proposed. 5,6) On the other hand, several calcium channel antagonists have also been reported to induce CYP2B and CYP3A subfamily enzymes in the rat liver [7][8][9] and human primary cultured hepatocytes.…”
mentioning
confidence: 99%
“…As a result, the availability of captopril was affected by concurrent administration of H 2 -receptor antagonists [8]. It has been reported that cimetidine reduces metabolism and increases steady state plasma concentrations of several concomitantly administered drugs [9]. Few, but contradictory, data are available on the effects of H 2 -blockers on ACE inhibitor pharmacokinetics [10].…”
Section: Introductionmentioning
confidence: 99%